(untitled) (Journal of Engineering, 2011)
In this paper a robust governor has been designed using H∞ techniques to replace the conventional governor of the steam turbine of the power system to regulate the frequency of the power grid. The robust governor is synthesized using state-space approach with time variations, neglected dynamics, and constant main steam pressure are considered in the design process. The proposed approach ensures internal stability, satisfying both frequency and time domains requirements, and obtaining minimal performance H∞-norm of the closed-loop system in one burden. The simulations are carried out using MATLAB and the results show that the overall system output performance can be improved using the proposed H∞ robust governor.